Results of european pooled analysis of IORT-containing multimodality treatment for locally advanced rectal cancer: adjuvant chemotherapy prevents local recurrence rather than distant metastases - Kusters, Miranda; Valentini, V.; Calvo, F. A.; Krempien, Robert; Nieuwenhuijzen, G. A.; Martijn, H.; Doglietto, G. B.; del Valle, E.; Röder, Falk; Büchler, Markus W.; van de Velde, C. J. H.; Rutten, H. J. T. (Annals of oncology, 2010)
Background - The purpose of this study is to analyze the pooled results of multimodality treatment of locally advanced rectal cancer (LARC) in four major treatment centers with particular expertise in intraoperative radiotherapy (IORT). - Patients and methods - A total of 605 patients with LARC who underwent multimodality treatment up to 2005 were studied. The basic treatment principle was preoperative (chemo)radiotherapy, intended radical surgery, IORT and elective adjuvant chemotherapy (aCT). In uni- and multivariate analyses, risk factors for local recurrence (LR), distant metastases (DM) and overall survival (OS) were studied. - Results - Chemoradiotherapy lead to more downstaging and complete remissions than radiotherapy alone (P < 0.001). In all, 42% of the patients received aCT, independent of tumor-node-metastasis stage or radicality of the resection. LR rate, DM rate and OS were 12.0%, 29.2% and 67.1%, respectively. Risk factors associated with LR were no downstaging, lymph node (LN) positivity, margin involvement and no postoperative chemotherapy. Male gender, preoperatively staged T4 disease, no downstaging, LN positivity and margin involvement were associated with a higher risk for DM. A risk model was created to determine a prognostic index for individual patients with LARC. - Conclusions - Overall oncological results after multimodality treatment of LARC are promising. Adding aCT to the treatment can possibly improve LR rates.